2008
DOI: 10.3113/fai.2008.0578
|View full text |Cite
|
Sign up to set email alerts
|

Neurectomy versus Neurolysis for Morton's Neuroma

Abstract: When treating Morton's neuromas surgically, neurolysis can be a valid option when a pseudoneuroma has not developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 6 publications
0
20
0
5
Order By: Relevance
“…Operative strategies range from neurectomy or neurolysis to neuroma excision with mobilization and burial of the proximal nerve. 5,6,22,23,28 Neurectomy and neurolysis have failed to yield durable pain relief, and extensive nerve mobilization for transposition and burial necessitates greater operative morbidity. 6,19,29 An ideal approach would limit the operative field to the site of injury, simplify intraoperative decision making, provide durable pain relief, and offer the potential to restore sensation.…”
Section: Introductionmentioning
confidence: 99%
“…Operative strategies range from neurectomy or neurolysis to neuroma excision with mobilization and burial of the proximal nerve. 5,6,22,23,28 Neurectomy and neurolysis have failed to yield durable pain relief, and extensive nerve mobilization for transposition and burial necessitates greater operative morbidity. 6,19,29 An ideal approach would limit the operative field to the site of injury, simplify intraoperative decision making, provide durable pain relief, and offer the potential to restore sensation.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing complaints about recurrences of the symptoms measured in a long-term follow-up may provide the answer to this question. The initial treatment of metarsalgia is mainly conservative [1][2][3]18] and includes the use of pads and orthopedic shoes, rehabilitation, and steroid and anesthetic injections [27,[29][30][31]. Makki et al [32] concluded that a single ultrasound-guided corticosteroid injection results in generally short-term pain relief for symptomatic Morton's neuromas.…”
Section: Discussionmentioning
confidence: 99%
“…If conservative methods fail, surgery should be performed, in which case there is a choice between neurolysis [18,19] and neurectomy through a dorsal approach [8,20,21] or a plantar approach [22][23][24].…”
mentioning
confidence: 99%
“…Da die Narbe an der Fußsohle bei Belastung des Fußes störend ist, und wegen der postoperativ erforderlichen stationären Behandlung, findet der dorsale Zugang zunehmend Verbreitung (Hassouna und Singh 2005). Villas et al (2008) fanden keinen Unterschied zwischen Dekompression und Resektion. Alternativ wurde von Gauthier (1979) eine Spaltung des Intermetatarsalbandes ohne Neuromresektion empfohlen, die wir gelegentlich durchgeführt haben, wenn kein eindeutiges Morton-Neurom erkennbar war.…”
Section: Anamneseunclassified